Effectiveness of Crawford Tube Implantation in Pediatric Age Group at Tertiary Care Hospital - Murtaza Sameen; Muhammad Shahid; Muhammad Awais; Muhammad Adnan; Fakhar Humayun; Asghar Rana (Pakistan Armed Forces Medical Journal, 2023)
Objective: To observe effectiveness of Crawford tube intubation in paediatric age group at tertiary care hospital. Study Design: Quasi experimental study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Apr 2021 to Apr 2022. Methodology: A sum of 25 subjects were included in this study ranging from 24 months to 72 months. After multiple failed probing subjects underwent bi-canalicular Crawford tube intubation under GA. After dilating punctum, Crawford tube was inserted from upper and lower punctum and passed through inferior meatus endoscopic guided and was knot in a square shaped. Tube remained in place for 3-6 months. Results: Out of 25 subjects, 8(32%) were males and 17(68%)were females who underwent Crawford tube intubation, there was 24(96%) success rate among children with endoscopic guided Crawford intubation. Follow-up was done up to 06 months. After 3-6 months in the absence of epiphora tube was removed. Failure was noticed in 1(4%) of cases due to tube dislodgement. Conclusion: Intubation in CNLDO with Crawford shows promising results among Pakistani population. Early treatment can effectively increase the success rates and reduces the fibrosis formation.